IMPROVEMENT OF WATER HYACINTH LEAFES MEAL (Eichhornia crassipes) FERMENTED WITH COW RUMEN LIQOUR AS FEED INGREDIENTS FOR JELAWAT(Leptobarbus hoeveni) SEEDS - Sella Nur Happy; Indra Suharman; Adelina Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT The research was conducted from August to December 2018. The research aims to evaluate improvement of the quality of Water Hyacinth Leaf Meal (WHLM) (Eichhornia crassipes) fermented with cow rumen liqour (CRL) as feed ingredients for jelawat (Leptobarbus hoeveni) seeds. The research was conducted in three stages. First stage: CRL activated with and without carbon as a WHML fermenter. The WHML proximate test results showed that the best treatment was CRL with the addition of carbon which produced 16.66% protein, 2.26% fat, 19.5% crude fiber and 13.44% ash. Second stage: CRL with the addition of carbon is used in different doses, by adding CRL 0, 100, 200, 300, 400 and 500 ml/kg WHML. Organoleptic and proximate tests showed that the best treatment was CRL 300 ml/kg WHML (P3) which produced a score of 3.73 aroma, 2.02 texture. Decreased crude fiber content from 20.04% to 16.80% and increased protein content from 11.315% to 13.32%, decreased fat content from 1.08% to 0.33%. Third stage: CRL treatment of 300 ml/kg WHML (P3) was tested for enzyme activity and digestibility of the ingredients. The highest enzyme activity was the amylase enzyme activity, namely 5.792 U/ml and 23.74-32.44% digestibility. Keywords : Water Hyacinth Leaves, Cow Rumen Liqour, Fermentation, Digestibility